ANALISIS SWOT DALAM STRATEGI PEMASARAN MUSEUM DE JAVASCHE BANK SURABAYA UNTUK MEMBANGUN CITRA POSITIF - Ningrum, Sasmitha Pitha; Rahmatin, Leily Suci (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
This research aims to describe the results of the SWOT analysis of promotional strategies carried out at the De Javasche Bank Museum Surabaya. This research was conducted using a qualitative descriptive approach. The informant used in this research was one person using a purposive sampling technique, namely the Public Relations division of Bank Indonesia or the management of the De Javasche Bank Surabaya Museum. Data collection was carried out using semi-structured interviews, observation and documentation. The data analysis used is using the SWOT analysis technique. The results of this research show that the De Javasche Bank Surabaya Museum's promotional strategy for the De Javasche Bank Surabaya Museum in building a company image is that the De Javasche Bank Surabaya Museum has carried out several marketing strategies, but some have not been optimized to date.